Meta Analisis Pengaruh Pendekatan Matematika Realistik Terhadap Hasil Belajar Siswa Sekolah Dasar - Ahmad Rustam; Waode Ekadayanti; Tanjung Niasari; Rahmat Rahmat (Journal on Education, 2023)
The purpose of this study is to evaluate the impact of the Realistics Mathematics method on the mathematics learning outcomes of primary school children. With the aid of the teacher, students may benefit from a greater grasp of the connection between mathematics and daily life thanks to the realistic mathematics method. Math issues are something that students can handle. The investigation was a meta-analysis investigation. the initial action taken in this investigation, which was problem formulation. The second stage entails using Google Scholar to look for study findings from online journals. The third phase is the analysis of the research data, and the research haul report comes last. Ten articles from journals relating to a topic were found from the search results. collected from publications that deal with realistic methods and primary school-level research. Thus, by using a realistic mathematical approach, students may comprehend how ideas relate to one another and how they apply to real-world situations. Ten publications that were pertinent to the realistic mathematical method were used to gather the study data. In a descriptive manner, it demonstrates how a practical mathematical method increased the average value from 59.29 to 83.44. The data from the pretest and posttest varied significantly. It was determined that primary school kids' learning results were impacted by a realistic mathematics approach